Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1186/s12888-016-1167-0
|View full text |Cite
|
Sign up to set email alerts
|

Neutropenia and agranulocytosis during treatment of schizophrenia with clozapine versus other antipsychotics: an observational study in Iceland

Abstract: BackgroundData on the haematological outcomes of patients who continue clozapine treatment following neutropenia are very rare as even mild neutropenia results in mandatory discontinuation of clozapine in most countries. However, in Iceland where clozapine monitoring is less stringent allows an observational study to be done on the risk of agranulocytosis and neutropenia during treatment with clozapine compared with other antipsychotics among patients with schizophrenia.MethodsThe present study is a part of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 22 publications
1
45
1
3
Order By: Relevance
“…It is the responsibility of the physician to organise these weekly laboratory investigations. To our knowledge, only one other study reported the frequency of neutrophil measurements after the initiation of clozapine, with measurements being performed during the first 18 weeks at a mean interval of 25 days (Ingimarsson et al 2016). This is less often than in our study.…”
Section: Comparison With Other Studiescontrasting
confidence: 53%
“…It is the responsibility of the physician to organise these weekly laboratory investigations. To our knowledge, only one other study reported the frequency of neutrophil measurements after the initiation of clozapine, with measurements being performed during the first 18 weeks at a mean interval of 25 days (Ingimarsson et al 2016). This is less often than in our study.…”
Section: Comparison With Other Studiescontrasting
confidence: 53%
“…In a study of patients with schizophrenia comparing those on long-term clozapine treatment versus non-clozapine antipsychotics, mild neutropenia (1.5-1.9 x10 9 /l) was significantly associated with clozapine compared with non-clozapine drugs (hazard ratio of 1.86). Moderate to severe neutropenia (0-1.4 x10 9 /l) on the other hand was more common in patients who had never been on clozapine despite having blood counts half as frequently as those on clozapine (Ingimarsson et al, 2016). The Iceland data suggest that many instances of neutropenia are probably unrelated to clozapine and very rarely progress to the more severe agranulocytosis.…”
Section: Discussionmentioning
confidence: 88%
“…37 Clozapine-induced neutropenia occurs in ∼1% of patients. In recent decades, it was found that patients with schizophrenia who take other antipsychotics had an equal risk of developing neutropenia as those taking clozapine [38]. Notable, neutrophils are mainly known for their proinflammatory role in anti-bacteria.…”
Section: Discussionmentioning
confidence: 99%